Reduction in Cesarean Delivery Rates Associated With a State Quality Collaborative in Maryland. Issue 4 (October 2021) - Callaghan-Koru, Jennifer A.; DiPietro, Bonnie; Wahid, Inaya; Mark, Katrina; Burke, Ann B.; Curran, Geoffrey; Creanga, Andreea A.
Abstract : OBJECTIVE: To assess the extent to which hospitals participating in the MDPQC (Maryland Perinatal-Neonatal Quality Care Collaborative) to reduce primary cesarean deliveries adopted policy and practice changes and the association of this adoption with state-level cesarean delivery rates. METHODS: This prospective evaluation of the MDPQC includes 31 (97%) of the birthing hospitals in the state, which all voluntarily participated in the 30-month collaborative from June 2016 to December 2018. Hospital teams agreed to implement practices from the "Safe Reduction of Primary Cesarean Births" patient safety bundle, developed by the Council on Patient Safety in Women's Health Care. Each hospital's implementation of practices in the bundle was measured through surveys of team leaders at 12 months and 30 months. Half-yearly cesarean delivery rates were calculated from aggregate birth certificate data for each hospital, and differences in rates between the 6 months before the collaborative (baseline) and the 6 months afterward (endline) were tested for statistical significance. RESULTS: Among the 26 bundle practices that were assessed, participating hospitals reported having a median of seven practices (range 0–23) already in place before the collaborative and implementing a median of four (range 0–17) new practices during the collaborative. Across the collaborative, the cesarean delivery rates decreased from 28.5% to 26.9% ( P =.011) for all nulliparous term singleton vertex births and from 36.1% to 31.3% ( P <.001) for nulliparous, term, singleton, vertex inductions. Five hospitals had a statistically significant decrease in nulliparous, term, singleton, vertex cesarean delivery rates and four had a significant increase. Nulliparous, term, singleton, vertex cesarean delivery rates were significantly lower across hospitals that implemented more practices in the "Response" domain of the bundle. CONCLUSION: The MDPQC was associated with a statewide reduction in cesarean delivery rates for nulliparous, term, singleton, vertex births. Abstract : The Maryland Perinatal-Neonatal Quality Care Collaborative was associated with reductions in cesarean delivery for nulliparous, term, singleton, vertex births.